Simulação e análise transitória de elevada integração de geração distribuída fotovoltaica em redes de distribuição - Costa, Ramon Frickes (2023)
The increasing demand for renewable sources of electric energy, with low environmental impact, has led to advancements in various fields, including Distributed Generation (DG), which represents an alternative generation model compared to the traditional centralized electricity supply system. However, excessive use of this technology can result in operational situations that did not occur previously in a conventional system, such as bidirectional power flow and significant variations in short-circuit current values. In this context, this work presents the use of a Simplified Photovoltaic Generator Model to analyze the high penetration impact of Distributed Photovoltaic Generation on the power, voltage and current profiles of the IEEE 13 Node Test Feeder during single-phase and three-phase faults using the ATP/ATPDraw software. The simplified modeling allows for faster and more efficient analyses while reducing computational effort. The presented results demonstrate that the current protection philosophy may be insufficient in systems with a high level of DG penetration, depending on the type of fault and the total power supplied by the Distributed Generators.